I've got the following grammar I'm attempting to convert to CNF.
S -> T01 | USV | epsilon U -> X V -> S1S | X | 1 X -> 0XS | 0 T -> TV | XT | UTU
I know that when I eliminate epsilon-productions I get...
S -> T01 | USV | UV U -> X V -> S1S | S1 | 1S | X | 1 X -> 0XS | 0X | 0 T -> TV | XT | UTU
I understand that we're getting rid of the epsilon but I don't really get what we're doing with the other symbols. For example how does S now produce
UV? If someone could explain this to me I'd really appreciate it.